Hubungan Kadar Glukosa Darah Puasa dengan Volume Prostat pada Pasien Benign Prostatic Hyperplasia - Flora Gracia Rumenta Siagian; Eka Yudha Rahman; Oski Illiandri (Homeostasis, 2020)
Abstract: Benign prostatic hyperplasia (BPH) is a common disorder in older men as the incidence increases with age. There are various theories mentioning risk factors of BPH, one of them is hyperglicemia and insulin resistance. The purpose of this study was to determine the relationship of fasting blood glucose levels with prostate volume in BPH patient. This research used analytic observational method with cross-sectional approach. Samples were taken by purposive sampling technique with the number samples of this study were 31 samples. Data analysis using Spearman correlation analysis. The result shows that the average prostate volume was 41.7 ± 11.3 cc. The average fasting blood glucose is 105.35 ± 17.03 mg / dl. There is a significant relationship between levels of fasting blood glucose with prostate volume in BPH patients with a weak degree of correlation. (r = 0.043, p = 0.366). Keywords: BPH, fasting blood glucose, prostate volume Abstrak: Benign Prostatic Hyperplasia (BPH) adalah penyakit yang umum diderita oleh pria usia tua dengan prevalens yang meningkat seiring pertambahan usia. Terdapat beragam teori mengenai faktor risiko yang berhubungan dengan BPH salah satunya adalah keadaan hiperglikemia dan resistensi insulin. Tujuan penelitian ini untuk mengetahui hubungan kadar GDP dengan volume kelenjar prostat pada pasien BPH Penelitian ini menggunakan metode penelitian observasional analitik dengan pendekatan cross-sectional. Sampel diambil dengan teknik purposive sampling dengan jumlah sampel penelitian didapatkan 31 sampel. Analisis data menggunakan uji korelasi Spearman. Hasil penelitian didapatkan rerata volume prostat di dapatkan 41.7 ± 11.3 cc. Rerata GDP didapatkan 105.35 ± 17.03 mg/dl. Terdapat hubungan yang bermakna antara kadar GDP dengan volume prostat pada pasien BPH dengan derajat korelasi lemah. (r=0.043, p=0.366). Kata-kata kunci: BPH, RFM, volume prostat